GEMA CERMAT (GERAKAN MASYARAKAT CERDAS MENGGUNAKAN OBAT) FOR STUDENT IN THE CITY OF KENDARI SOUTHEAST SULAWESI - Suryani Suryani; L.O.M Fitrawan; Waode Sukmawati Arsyad; Rina Andriani; Rini Hamsidi (Darmabakti Cendekia: Journal of Community Service and Engagements, 2020)
Background: The problem of rational use of drugs in the community, especially among students, still not many know or still lack of knowledge. The careful echo is a joint effort of the government and the community through a series of activities in realizing the awareness, awareness, understanding and community skills in using drugs appropriately and correctly. Purpose: This activity aims as an effort to improve understanding, knowledge and awareness of the community, especially students about the use of appropriate and correct medicines by providing training in the skills to choose and use drugs properly for self-medication so that drug abuse does not occur as a manifestation of the Program of Echoing Careful. Method: The method to be used in increasing knowledge was the Active Learning method (CBIA). This method was an educational model of community empowerment to be more skilled in choosing drugs so that self-medication becomes more effective, safe, and cost-effective. Results: The result of this program was an increase in student understanding of the types of drugs, forms of drug preparation, and independence in choosing, obtaining, using, storing, and destroying / disposing of drugs correctly and appropriately. Conclusion: The Schematic Echoes Program (GeMa CerMat) increased student knowledge about rational use of drugs and self-medication (Swamedikasi) through how to properly manage drugs, use and choose drugs correctly, and or how to see their efficacy and side effects.